A semi-empirical approach for estimating the lateral earth pressure on rigid retaining walls with EPS inclusions in cohesionless soils. (March 2023) - Han, Zhong; Zou, Wei-lie; Ying, Zhen-qian; Feng, Huai-ping; Yang, Guang-qing
Abstract: Placing the expanded polystyrene (i.e. EPS) as inclusions between the rigid nonyielding wall and fill enables the lateral displacement of the fill and renders the lateral earth pressure from the at-rest state to the active state. This effectively alleviates the lateral load and facilitates cost-effective designs for rigid retaining walls. This study develops a semi-empirical approach to predict the lateral earth pressure on rigid retaining walls with EPS inclusions in cohesionless soils. This approach is simple and requires only conventional soil and EPS properties for prediction. Its performance is validated by the results of different physical and numerical modeling studies with EPS inclusions of various densities and thicknesses. It is demonstrated that (i) the lateral earth pressure depends on the stiffness of the EPS inclusions (i.e. the ratio of the elastic modulus to the thickness), and (ii) EPS inclusions with a single and proper thickness can fulfill the majority of load reduction purposes. Suggestions for the choices of (i) the EPS materials in terms of density and elastic modulus, (ii) the thickness of EPS inclusions, and (iii) the structure of the EPS inclusions are proposed for the use of EPS inclusions in cohesionless soils.